Pelatihan Pengembangan Pembelajaran Online untuk Guru-Guru di SMA 2 Bogor - Rhini Fatmasari; Kadarisman Kadarisman; Untung Laksana Budi; Ade Mardiana (ABDI: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2022)
The current paradigm shift in learning has resulted in demands for increased teacher competence, especially in the field of information technology. The Covid pandemic has caused a change from face-to-face learning to online learning. Learning Management System (LMS) is a platform to support online learning. The Open University Lecturer Community Service Program is the development of the Learning Management System (LMS) of SMAN 2 Bogor and online learning training with 85 teachers participating. The first stage of the LMS SMAN 2 Bogor platform that has been developed includes features a) attendance list; (b) learning modules; (c) value; (d) assignment assessment, and (e) feedback. LMS SMAN 2 Bogor will then be developed again in the community service program the following year.